Integral Chemical Waste Management in Laboratories - Loayza P., Jorge (2005)
The suitable management and handling of the chemical wastes origínatíng from laboratories allow the saving of reagents and materíals; as well as the reductíon of costs assocíated wíth their handling and final disposal. lt also prevents detriment to the health of the people who have to conduct an academic activity in the laboratory (professors, assistants and students) ora professíonal activity related to service consulting dealíng with chemical analyses (analysts, assistants and auxiliary personnel). The responsible handling of chemícal wastes wíll reduce present and future threats to the health and the environment; as well as the deterioration of materials. Therefore, a method far envíronmental chemical waste management of laboratories is presented.